2015
DOI: 10.1007/s12237-015-9998-3
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Understanding the Effects of Sediment Dynamics on Oyster Reef Development

Abstract: Previous field studies have demonstrated that sedimentation is an important factor that can limit oyster reef growth and restoration success. High relief reefs are more productive and resilient than low relief reefs, in part, because increasing reef height reduces sedimentation and enhances oyster growth. In this study, we investigated the relationship between initial reef height and reef development using a simple model. The model contains three coupled differential equations that describe changes in oyster v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…If flow rates are sufficient to promote sediment erosion from the reef and break down feeding-inducing concentration gradients, this could result in increased recruitment, growth, and survival of the oyster population (Lenihan 1999, Byers et al 2015. Jordan-Cooley et al (2011) suggest a bifurcation point for reef populations above which reefs and live oyster populations increased to a non-zero equilibrium and persisted over time and below which reefs were overwhelmed by sediment and degraded to extinction in less than 20 yr. Other models demonstrate similar dynamics to those described by Jordan-Cooley et al (2011) in response to different initial reef height conditions (Wil berg et al 2013, Housego & Rosman 2016.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…If flow rates are sufficient to promote sediment erosion from the reef and break down feeding-inducing concentration gradients, this could result in increased recruitment, growth, and survival of the oyster population (Lenihan 1999, Byers et al 2015. Jordan-Cooley et al (2011) suggest a bifurcation point for reef populations above which reefs and live oyster populations increased to a non-zero equilibrium and persisted over time and below which reefs were overwhelmed by sediment and degraded to extinction in less than 20 yr. Other models demonstrate similar dynamics to those described by Jordan-Cooley et al (2011) in response to different initial reef height conditions (Wil berg et al 2013, Housego & Rosman 2016.…”
Section: Introductionmentioning
confidence: 62%
“…Population models suggest that sediment deposition mediated by initial reef height is capable of producing alternative stable equi libria similar to reef outcomes observed in the field (JordanCooley et al 2011, Wilberg et al 2013, Housego & Rosman 2016. In these models, a stable, non-zero equilibrium is achieved when live oyster and shell volume growth outpaces sediment de position, which varies with reef height and reaches a maximum at the seafloor (Jordan-Cooley et al 2011, Housego & Rosman 2016.…”
Section: Mechanisms and Positive Feedbacksmentioning
confidence: 78%
See 1 more Smart Citation
“…, Nystrom et al. , Housego and Rosman ). In systems with alternative stable states, restoration becomes particularly challenging as transitions between desired and undesired states can occur through sudden, often unpredictable, phase shifts, and successful restoration often requires the conditions of the system be returned to levels more extreme than those immediately prior to the phase shift (Scheffer et al.…”
Section: Introductionmentioning
confidence: 97%
“…Demographic modeling has shown that positive feedbacks between living oysters and shell substrate can lead to thresholds between population persistence and extinction, as well as possible alternative stable states (Jordan-Cooley et al 2011, Nystrom et al 2012, Housego and Rosman 2016. In systems with alternative stable states, restoration becomes particularly challenging as transitions between desired and undesired states can occur through sudden, often unpredictable, phase shifts, and successful restoration often requires the conditions of the system be returned to levels more extreme than those immediately prior to the phase shift (Scheffer et al 2001, Beisner et al 2003, Scheffer and Carpenter 2003, Hastings and Wysham 2010.…”
Section: Introductionmentioning
confidence: 99%